Application and comparison of three multiobjective linear programming methods (2011)
A biobjective production planning problem was modelled using the Compromise Constraint Biobjective LP (CCBLP) method, the traditional Weighted-sum Scalarization (WSS) and Non-preemptive Goal Programming (NGP) approaches. Various preference indices were used to explore the tradeoff options and the L1 distance metric was used to determine the best compromise solution and the appropriate preference indices. The solution of CCBLP was the closest to the ideal solution with L1 metric of 0.326 and corresponding preference indices of W1 = 0.25, W2 = 0.75. Comparison of the results showed that the CCBLP is more sensitive to changes in preference indices than the WSS and NGP methods and hence it is more useful in helping the decision maker to make intelligent tradeoff decisions